The economic viability of a bee breeding project and adrift proposal - عبد, حميد عبيد; جبر, مأمون احمد; عويد, عايد نعمه (Journal of Economics and Administrative Sciences, 2012)
Bee keping projects is one of the most important agricltural investment projects because it generate profit in a short period . In addition to the multiplicity of products and other benefits . Research aimed at study the feasibility of two projects one hand in the origin of the Al – Mashrok since 2006 , kicking off with ten hives , and the scond proposal , kicking of 100 hives using the criteria of the world bank . Results showed that the bee keeping projects is economically feasible, whether small or large .. Even when the analysis of the sensitivity of the project to changes which may occur in the price of output and resources by reducing costs and increasing revenues by 10% it remains economically viable . It is there fore imperative that the state support bee keeping projects and provide the necessary facilities , for the development of rural areas and tap the potential of youing peoples and operate  in such projects . As well as the multiplicity of products and other economic benefits , and interacting with industries . The internal rate of return than the interest rates three times in the marketans more